Effect of adding coconut shell charcoal powder on clay impermeable layer small dam core material - Yuniasari, Trisyanita; Rusdiansyah, (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Clay soil is widely chosen to be used as a waterproof core layer material in ponds because there is a tendency to have water-tight properties. However, in general conditions, clay soil has several weaknesses and causes problems in civil construction, such as low shear strength and high plasticity. The existence of this condition is certainly a consideration to improve the mechanical properties of the clay when it is to be used as a waterproof core layer in the reservoir. This effort is carried out to increase the shear strength of the soil and reduce its permeability so that it can meet the requirements as soil for an impermeable core layer. The permeability coefficient for the minimum pond core material is less than or equal to 1x10-6 cm/sec. In this study, coconut shell charcoal was used as a stabilizing agent for clay soil. The percentage variations of the coconut shell charcoal mixture used were 0%, 5%, 10%, 15%, and 20%. This study aims to determine the effect of coconut shell charcoal powder on the permeability coefficient, and the shear strength of clay soil which will be used as the core material of the watertight reservoir. The tests carried out in this study were atterberg limit testing, grain gradation analysis, compaction, shear strength, and permeability. Based on the results of testing with soil samples varying from a mixture of 0% to 20% coconut shell charcoal, it was found that the best addition of coconut shell charcoal for shear strength testing was a mixture variation of 15% with a cohesion value of 0.353 kg/cm2 and a mixture variation of 20 % with a sliding angle value of 43.2580. Whereas in the permeability test on the coconut shell charcoal mixture of 15% is the best addition of coconut shell charcoal with a permeability coefficient of 2.106x10-7 cm/second.